Razkorak v opredeljevanju na anketna vprašanja - Novak, Meta (Družboslovne razprave, 2013)
The knowledge gap hypothesis states that with the infusion of mass media information the knowledge gap between the information rich and the information poor is widening. Besides the knowledge gap, we can talk about the response gap in survey questions. Using data from the European Social Survey 2010, we seek to test whether the model for explaining the knowledge gap can also be used to explain the response gap in survey questions. Even though the model was not strongly confirmed, it turned out to be useful for explaining the share of nonresponses in the sample of the whole survey (27 European countries) as well as for the case of Slovenia. In the case of Slovenia, the response gap was explained by an interest in politics and education level and not by media attendance.
Keywords: Družboslovne ankete; Social surveys; Slovenia; Slovenija; razkorak v opredeljevanju; knowledge; znanje; politično znanje; razkorak v znanju; ankete